Media Penyuluhan Managemen Laktasi Saat Pandemi - Rabia Zakaria; Siti Choirul Dwi Astuti (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
During the pandemic babies should get breast milk because it has a high risk compared to the general population. Knowledge of lactation management during the pandemic is very necessary because it will determine the success of mothers in breastfeeding. However, in a pandemic situation direct counseling on lactation management cannot be done because it must keep a distance. Therefore, effective media is needed for counseling without making direct contact. The purpose of the research is to find out the most appropriate media to provide counseling on lactation management during the pandemic. This research is based on methods including correlation studies with quantitative approaches. Respondents in the study used 30 nursing mothers in Padengo Village and Poowo Village, Bone Bolango Gorontalo Regency. Respondents were taken randomly. The measuring instrument uses 30 questions that have been conducted validity and reliability tests. Respondents were given three different media for counseling on lactation management while breastfeeding, namely books, leaflets and powerpoints. Then knowledge is measured by questionnaires. As a result, the average knowledge of mothers who are given counseling using animated book media is better than leaflets and powerpoints. The results of the data analysis using Anova Test averaged the value of maternal knowledge given by the book media had the highest score of 23.90. Which means books are better for improving breastfeeding mothers' knowledge of lactation management compared to leaflets and powerpoints.